Reliability of quantitative ultrasound measures of the biceps and supraspinatus tendons. - Collinger JL; Gagnon D; Jacobson J; Impink BG; Boninger ML; Collinger, Jennifer L; Gagnon, Dany; Jacobson, Jon; Impink, Bradley G; Boninger, Michael L (Academic Radiology, 2009)
Rationale and Objectives: Ultrasound is a proven method for examining soft tissue structures, including tendons, and recently quantitative ultrasound has become more prevalent in research settings. However, limited reliability data have been published for these new quantitative ultrasound measures. The main objective of this study was to quantify the reliability and measurement error of multiple quantitative ultrasound imaging protocols for the biceps and supraspinatus tendons.Materials and Methods: Two examiners captured ultrasound images of the non-dominant long head of the biceps tendon and supraspinatus tendon from 15 able-bodied participants and five manual wheelchair users. Each examiner captured two images per subject under two different preparations, which included subject positioning and reference marker placement. Image processing (reading) was performed twice to compute nine quantitative ultrasound measures of grayscale tendon appearance using first-order statistics and texture analysis. Generalizability theory was applied to compute interrater and intrarater reliability using the coefficient of dependability (Phi) for multiple study design protocols.Results: Interrater reliability was generally low (0.26 < Phi < 0.82), and it is recommended that a single evaluator capture all images for quantitative ultrasound protocols. Most of the quantitative ultrasound measures (n = 14 of 18) exhibited at least moderate (Phi > 0.50) intrarater reliability for a single image captured under one preparation and read once.Conclusion: By following a protocol designed to minimize measurement error, one can increase the reliability of quantitative ultrasound measures. An appropriately designed protocol will allow quantitative ultrasound to be used as an outcome measure to identify structural changes within tendons.